(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
English has become one of the most important international languages, playing a significant role in education, business, science, and communication. Consequently, English language teaching has shifted from traditional teacher-centered instruction to more student-centered and interactive approaches. Interactive teaching methods encourage learners to actively participate in classroom activities, improve communication skills, and develop higher-order thinking abilities. This paper explores the importance